In Vivo Antiviral Properties of Biologically Active Compounds: II. Studies with Influenza and Vaccinia Viruses - Sidwell, Robert W. (1968)
The in vivo anti-influenza virus and antivaccinia virus activity of 156 biologically active compounds was determined. One of two criteria was used for evaluating activity against the influenza virus. The criteria were increase in survivor number and mean survival time, and reduction in virus-induced lung consolidation in treated, infected Swiss mice. Increase in survivor number and mean survival time were the criteria for evaluation of antivaccinia virus activity. Several drug doses were tested against two virus concentrations to demonstrate antiviral activity more clearly. Two compounds were considered significantly active against the influenza virus: DL-noformicin (NSC 72942) and amantadine hydrochloride (NSC 83653). Eleven compounds had reproducible activity against vaccinia virus: isatin-β-thiosemicarbazone (NSC 721), 6-azauracil (NSC 3425), 9-α-fluoro-2α-methylhydrocortisone 21-acetate (NSC 12601), 5-[bis(2-chloroethyl)amino]uracil (NSC 34462), 5-iodo-2′-deoxyuridine (NSC 39661), streptonigrin (NSC 45383), N-methylisatin β-thiosemicarbazone (NSC 69811), cytovirin (NSC 91770), 9-β-D-arabinofuranosyladenine (NSC 404241), and 5-(mercaptomethyl)uracil (NSC 529351).